2020
DOI: 10.1523/eneuro.0474-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte-Mediated Tissue Repair through PDGFRβ Promotes Peri-Infarct Astrogliosis, Oligodendrogenesis, and Functional Recovery after Acute Ischemic Stroke

Abstract: Visual Abstract Significance StatementPericyte-mediated fibrotic tissue repair is a major histological change within the infarct area during the subacute phase after ischemic stroke. Whether fibrotic repair is beneficial or detrimental to post-stroke functional recovery is highly debated. Here, we demonstrate that inhibition of fibrotic repair in mice by heterozygous deletion of platelet-derived growth factor receptor b (PDGFRb ) (Pdgfrb 1/-) significantly attenuates functional recovery after ischemic stroke. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 65 publications
4
65
0
Order By: Relevance
“…Whether a pericyte-mediated fibrotic response following brain injury contributes to neural repair and functional recovery is still under debate [ 83 , 84 ]. However, increasing evidence shows that fibroblastic-like cells derived from brain pericytes produce trophic factors and promote neural repair by promoting astrogliosis and oligodendrogenesis following ischemic stroke [ 16 , 85 ], suggesting that they provide a beneficial nursing effect for post-ischemic brains.…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether a pericyte-mediated fibrotic response following brain injury contributes to neural repair and functional recovery is still under debate [ 83 , 84 ]. However, increasing evidence shows that fibroblastic-like cells derived from brain pericytes produce trophic factors and promote neural repair by promoting astrogliosis and oligodendrogenesis following ischemic stroke [ 16 , 85 ], suggesting that they provide a beneficial nursing effect for post-ischemic brains.…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Inmentioning
confidence: 99%
“…In addition, we found that, compared with permanent ischemia, reperfusion during stage II increased the number of iSCs and/or NSPCs within and around ischemic areas, and promoted the production of neurons, astrocytes, and oligodendrocytes [ 25 ]. Therefore, early reperfusion has the potential to promote healing processes, including neurogenesis and gliogenesis via various vascular cell-mediated mechanisms, such as endothelial-derived nursing effects [ 23 , 24 ], pericyte-derived nursing effects [ 16 , 85 ], and pericyte-derived transdifferentiation into neural lineages [ 21 , 22 , 62 ]). Furthermore, compared with permanent ischemia, immunohistochemical findings at the chronic phase (post-stroke day 56) indicate that reperfusion after lethal ischemia increased the number of not only vascular lineages (including endothelial cells and pericytes), but also neural lineages (including neurons and glia) [ 25 ].…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Inmentioning
confidence: 99%
“…Similarly, in mice subjected to permanent MCAo, pericytes within the infarct area produced trophic factors activating astrocytes, thereby enhancing peri-infarct astrogliosis (Shibahara et al, 2020). This interplay between astrocyte and microglial and/or pericytes following ischemia remains elusive.…”
Section: Effects Of Stroke On Astrocyte Structurementioning
confidence: 99%
“…-Leakage of blood-borne factors into brain parenchyma results in rapid microglia activation that enwrap and phagocytose ECs in the peri-infarct region. Chow et al, 2001;Hangai et al, 2002;Beck et al, 2008;Krum et al, 2008;Yu et al, 2010;Yenari et al, 2010;Jiao et al, 2011;Ben-Zvi et al, 2014;ElAli et al, 2014;Knowland et al, 2014;Jolivel et al, 2015;Choi et al, 2016;Nahirney et al, 2016;Thomsen et al, 2017;Underly et al, 2017;Eldahshan et al, 2019;Howe et al, 2019;Munji et al, 2019;Yao, 2019;Shibahara et al, 2020. Hemorrhagic stroke -ECs proliferate around hematoma following ICH.…”
Section: Regulation Of Angiogenesis Following Stroke Lessons From Devmentioning
confidence: 99%
“…While the role of PDGF signaling in the blood-brain barrier is not yet fully understood, several lines of evidence demonstrate that PDGF signaling increases blood-brain barrier permeability, resulting in neuronal damage, while others have demonstrated positive effects of PDGF signaling on blood-brain barrier function and recovery after neuronal insults. Examples of the impact, both positive and negative, of PDGF signaling have been reported for stroke [52][53][54] , HAND [24,55,56] , Alzheimer's disease (AD) [57] , Parkinson's disease (PD) [58] , epilepsy [59] , and neuroinflammation [60,61] .…”
Section: A Note On the Blood-brain Barriermentioning
confidence: 99%